2012
DOI: 10.1530/joe-12-0144
|View full text |Cite
|
Sign up to set email alerts
|

A description of large-scale metabolomics studies: increasing value by combining metabolomics with genome-wide SNP genotyping and transcriptional profiling

Abstract: The metabolome, defined as the reflection of metabolic dynamics derived from parameters measured primarily in easily accessible body fluids such as serum, plasma, and urine, can be considered as the omics data pool that is closest to the phenotype because it integrates genetic influences as well as nongenetic factors. Metabolic traits can be related to genetic polymorphisms in genome-wide association studies, enabling the identification of underlying genetic factors, as well as to specific phenotypes, resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Thus, it can be concluded that even if not cell-specific, the signals derived from whole blood data still reflect organism-wide processes. This is also in line with previous studies conducted on whole blood transcriptomics or metabolomics data separately [1,30,31]. …”
Section: Introductionsupporting
confidence: 92%
“…Thus, it can be concluded that even if not cell-specific, the signals derived from whole blood data still reflect organism-wide processes. This is also in line with previous studies conducted on whole blood transcriptomics or metabolomics data separately [1,30,31]. …”
Section: Introductionsupporting
confidence: 92%
“…These studies usually focus on organismal phenotypes [2][6]. Recently however, molecular phenotypes, including gene-expression [7], [8] and metabotypes [9][14], have also been investigated. Studying the effects of genetic variations on molecular phenotypes is motivated by two characteristics common to the vast majority of GWAS on organismal phenotypes: first, the biological mechanisms underlying the associations are often unknown; and second, the significantly associated loci individually explain only a small fraction of variability of the organismal phenotype, and even cumulatively fall far from explaining the estimated heritability of the phenotype [15].…”
Section: Introductionmentioning
confidence: 99%
“…Future technology development combined with more robust data analysis and bioinformatic tools will help overcome current limitations and fully integrate small molecule biochemistry with systems biology. Because metabolomics is complementary to genomics, transcriptomics, and proteomics, the full integration of these fields is the basis of systems biology, and only their combined application will enable for a full description of a living system at all biomolecular levels (Homuth et al, 2012;Lindon et al, 2006;Richards et al, 2010).…”
Section: Comparison Of Metabolomics With the Other ''Omics''mentioning
confidence: 99%